THE INFLUENCE OF SERVICE LEADERSHIP ON AFFECTIVE COMMITMENT AND ITS IMPLICATIONS ON THE PERFORMANCE OF STIE LECTURER IN MEDAN CITY - Cen, Cia; Amrizah, Azizul; Kamaluddin (Faculty of Economic and Business, University of Pasundan, 2024)
This study aims to determine the Effect of Serving Leadership, Compensation, Work Environment, on Tension and Affective Commitment and its implications on the work of STIE in Medan City, North Sumatra Province. The research method used is associative research, which is research conducted with the aim of determining the relationship or influence of more variables, namely the influence of independent variables on dependent variables using intervening variables. This research uses quantitative data sourced from primary, secondary and tertiary data. The data collection technique carried out is by interview techniques and questionnaires. The results of the study stated that there is a significant influence between Servant Leadership, Compensation, Work Environment, on Tension and Affective Commitment and its implications on Serving Leadership, Compensation, Work Environment, on Tension and Affective Commitment and its implications on Serving Leadership.